The Effect of Obstructive Sleep Apnea on DNA Damage and Oxidative Stress - Il Gyu Kang; Joo Hyun Jung; Seon Tae Kim (Clinical and Experimental Otorhinolaryngology, 2013)
ObjectivesObstructive sleep apnea syndrome (OSAS) is associated with repeated hypoxia and re-oxygenation. This characteristic of OSAS may cause oxidative stress and DNA damage. However, the link of OSAS with oxidative stress and DNA damage is still controversial. In the current study, we investigated whether OSAS causes DNA damage using alkaline single-cell gel electrophoresis (comet assay) and measuring oxidative stress by monitoring serum malondialdehyde (MDA) levels.MethodsFrom March 2009 to August 2010, 51 patients who underwent polysomnography (PSG) during the night were enrolled in this study. We obtained serum from the patients at 6 AM. DNA damage and oxidative stress were evaluated using a comet assay and measuring serum MDA, respectively. We divided the patients into two groups according to the existence of comets appearing in the comet assay. Group 1 included 44 patients with negative assay results and group 2 consisted of seven patients with positive comet assay findings. We compared the age, gender proportion, PSG data (respiratory disturbance index [RDI], lowest O2 saturation level, and arousal index [AI]), time of disease onset, smoking habits, and serum MDA levels between the two groups.ResultsThe average age and gender proportion of the two groups were not statistically different (P>0.05). The average of RDI for group 1 was 30.4±18.4 and 8.0±7.7 (P<0.01) for group 2. The average of lowest O2 saturation level for group 1 was 81.2±7.2 and 87.4±6.5 (P<0.05) for group 2. The average AI for group 1 was 32.8±15.1 and 20.8±7.7 (P<0.05) for group 2. Similarly, serum MDA levels of the two groups were not statistically different (P>0.05). No relationship between positive comet assay results and OSAS severity was identified.ConclusionResults of the current study showed that OSAS was not associated with DNA damage as measured by comet assays or oxidative stress according to serum MDA levels.